2019
DOI: 10.1097/cm9.0000000000000098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol, dexmedetomidine, and midazolam on postoperative cognitive dysfunction in elderly patients

Abstract: Background: Postoperative cognitive dysfunction (POCD) is a serious complication after surgery, especially in elderly patients. The anesthesia technique is a potentially modifiable risk factor for POCD. This study assessed the effects of dexmedetomidine, propofol or midazolam sedation on POCD in elderly patients who underwent hip or knee replacement under spinal anesthesia. Methods: The present study was a prospective randomized controlled preliminary trial. From July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 31 publications
5
82
0
2
Order By: Relevance
“…However, a lot of patients with LC who underwent VATL and dexmedetomidine experienced many complications, such as EPPNCD. [ 17 24 ] In addition, few data are available regarding the dexmedetomidine on EPPNCD after VATL in elderly male patients with LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a lot of patients with LC who underwent VATL and dexmedetomidine experienced many complications, such as EPPNCD. [ 17 24 ] In addition, few data are available regarding the dexmedetomidine on EPPNCD after VATL in elderly male patients with LC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 21 ] Studies suggested that it can benefit EPPNCD after VATL. [ 22 24 ] However, there is still limited data available regarding the efficacy and safety of dexmedetomidine on EPPNCD after VATL in elderly male patients with LC. Thus, this retrospective study investigated the efficacy and safety of dexmedetomidine on EPPNCD after VATL in elderly male patients with LC.…”
Section: Introductionmentioning
confidence: 99%
“…[1922] Even the use of anticoagulant and other alternative analgesics can reduce the side effects, not every patient is completely satisfied. [23,24] So the development of non-pharmacologic and alternative interventions is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Во-первых, мидазолам угнетает дыхание, в особенности при внутривенном введении и комбинации с опиоидами [50,51]. Во-вторых, у возрастных пациентов и с измененным когнитивным фоном мидазолам может вызвать послеоперационную когнитивную дисфункцию или даже делирий [52]. Недавно FDA официально распространило предупреждение о возможном эффекте бензодиазепинов -развитии послеоперационной когнитивной дисфункции, о чем рекомендуется информировать пациентов перед операцией.…”
Section: обзоры Reviewsunclassified